Die Landwirtschaft im Irak - Kellersohn, Heinrich (ERDKUNDE, 1953)
Divergent natural conditions have produced three distinctive land utilisation regions in Iraq. In the north and north-west, there is arable farming without irrigation, in the south raising of crops with irrigation, and in western and central Iraq, except in the main river valleys, nomadic animal husbandry is practised. The importance of agriculture in Iraq's national economy is remarkable. Even allowing for an increase in the income from mineral oil it is estimated that agricultural products will supply about 30 per cent, of the income from exports in 1953 and the following years. Nevertheless, crop yields are still low. To a certain degree, this is the result of unfavourable physical conditions. The main reason, however, can be found in the social shortcomings due to the fact that no legislative steps were taken to regulate land tenure while the economy changed from subsistence farming to farming for export. The consequences of this omission are most clearly visible in southern Iraq. Agricultural progress depends first and foremost on a thorough land reform which guarantees justice and security to the small-holders. The second preliminary for a far reaching improvement lies in the development of irrigation facilities.